C–H Functionalization Reactions of Phenyl and Vinyl Carbocations Paired with Weakly Coordinating Anions - Popov, Stasik; Shao, Brian; Bagdasarian, Alex L.; Wigman, Benjamin; Nelson, Hosea M. (Synlett, 2020)
Carbocations have played a central role in the chemical sciences for over a century. In a synthetic setting, most methods utilize stabilized tricoordinate carbocations, while there are far fewer examples of reactions featuring nonstabilized dicoordinate cations. Here, we provide an overview of recent developments in the generation of high-energy carbocations mediated by weakly coordinating anions and the C–H insertion reactions of such carbocations. Moreover, we discuss mechanistic studies of these catalytic C–H insertion reactions aimed at furthering our understanding of the reactive nature of these rarely invoked cationic intermediates.1 Introduction2 Background: Phenyl Carbocations3 Silylium/Carborane-Catalyzed C–H Insertion Reactions of Phenyl Carbocations4 Silane-Fueled, Weakly Coordinating Anion-Catalyzed, Reductive C–H Insertion Reactions of Vinyl Carbocations5 C–H Insertion Reactivity of Vinyl Carbocations under Basic Conditions6 Conclusion and Outlook
Keywords: carbocations; weakly coordinating anions; C–H insertion reactions; catalysis; C–H functionalization; organocatalysis